WSV056 Inhibits Shrimp Nitric Oxide Synthase Activity by Downregulating Litopenaeus vannamei Sepiapterin Reductase to Promote White Spot Syndrome Virus Replication - Wang, Wei; Zheng, Qin; Yu, Chen; Pan, Changkun; Luo, Peng; Chen, Jianming (Frontiers in Microbiology, 2021)
Sepiapterin reductase (Spr) plays an essential role in the biosynthesis of tetrahydrobiopterin (BH4), a key cofactor of multiple enzymes involved in various physiological and immune processes. Suppression of Spr could result in BH4 deficiency-caused diseases in human and murine models. However, information on the biological function of Spr in invertebrates is limited. In this study, two Sprs (CG12116 and Sptr) from Drosophila melanogaster were found to be downregulated in transgenic flies overexpressing white spot syndrome virus (WSSV) immediate-early protein WSV056. CG12116 and Sptr exerted an inhibitory effect on the replication of Drosophila C virus. A Litopenaeus vannamei Spr (LvSpr) exhibiting similarity of 64.1%–67.5% and 57.3%–62.2% to that of invertebrate and vertebrate Sprs, respectively, was cloned. L. vannamei challenged with WSSV revealed a significant decrease in LvSpr transcription and Spr activity in hemocytes. In addition, the BH4 co-factored nitric oxide synthase (Nos) activity in shrimp hemocytes was reduced in WSSV-infected and LvSpr knockdown shrimp, suggesting WSSV probably inhibits the LvNos activity through LvSpr downregulation to limit the production of nitric oxide (NO). Knockdown of LvSpr and LvNos caused the reduction in NO level in hemocytes and the increase of viral copy numbers in WSSV-infected shrimp. Supplementation of NO donor DETA/NO or double gene knockdown of WSV056 + LvSpr and WSV056 + LvNos recovered the NO production, whereas the WSSV copy numbers were decreased. Taken together, the findings demonstrated that LvSpr and LvNos could potentially inhibit WSSV. In turn, the virus has evolved to attenuating NO production via LvSpr suppression by WSV056, allowing evasion of host antiviral response to ensure efficient replication.